Relation between clinical best practices and 6-month outcomes after transcatheter aortic valve implantation with CoreValve (from the ADVANCE II study) - Sinning, Jan-Malte; Bekeredjian, Raffi (The American journal of cardiology, 2017)
Best practices for transcatheter aortic valve implantation with CoreValve include patient screening and valve size selection using multislice computed tomography, adherence to manufacturer recommendations for oversizing, control of implant depth to 6 mm or less, and management of conduction disturbances according to international guidelines. The ADVANCE II study implemented these strategies and demonstrated their relation to clinical outcomes. From October 2011 to April 2013, 200 patients with severe aortic stenosis were enrolled, and 194 were implanted. All imaging and electrocardiographic data were analyzed by an independent core laboratory, and adverse events were adjudicated to valve academic research consortium-2 definitions. The mean age was 80.2 ± 6.7 years and the mean Society of Thoracic Surgeons Predicted Risk of Mortality was 7.2 ± 6.8% for the enrolled patients. At 6 months, all-cause mortality was 9.2%, stroke was 2.6%, and permanent pacemaker implantation was 19.2% for class I and II indications. In patients with implant depth ≤6 mm, both mortality and permanent pacemaker implantation were lower than in patients with depth >6 mm (2.5% vs 14.5%, p <0.01 and 18.1% vs 31.7%, p = 0.03, respectively). The rate of moderate and severe paravalvular leak was 9.8% at 7 days after transcatheter aortic valve implantation, decreasing to 4.3% at 6 months (p = 0.02). Valves were significantly more oversized in patients with mild or less paravalvular leak at day 7 compared with those with moderate or severe (15.8 ± 8.0% vs 11.8 ± 4.9%, p = 0.01). In conclusion, findings from the ADVANCE II study reinforce that adherence to best clinical practices improves patient outcomes.